Exploring the factors influencing the co-pyrolysis of walnut shells, pistachio shells, and polypropylene based on thermal behavior, kinetics and reaction mechanism - Zhigang Huang; Tong Zhang; Chen Wang; Wenbo Xiao; Zihan Wang; Obid Tursunov; Jiahui Wu; Yuguang Zhou; Xiaolong Yao; Gang Li (Case Studies in Thermal Engineering)
The complex co-pyrolysis process of biomass with polypropylene (PP) and the limited research on microscopic reaction mechanisms have hindered its advance application in mitigating environmental issues and addressing the supply-demand imbalance of fossil fuels. In this study, walnut shells (WS) and pistachio shells (PS) were chosen as representative biomass materials to systematically investigate their co-pyrolysis characteristics with PP. Model-free isoconversional methods such as Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, Starink and Vyazovkin, were employed to analyze pyrolysis kinetics. The results demonstrate that the synergistic effect between PS and PP significantly decreased the activation energy of the reaction system (460.64–112.80 kJ/mol). Product analysis showed that the feedstock ratio and pyrolysis temperature had a significant effect on the composition of the product. The experimental findings indicated that at 600 °C with a PS:PP ratio of 1:2, the activation energy was minimized while the total content of phenols and hydrocarbons reached its highest level (75.42 %). By integrating thermogravimetric, kinetic, and product analyzes, this study establishes a comprehensive characterization system for understanding pyrolysis processes at multiple scale levels, providing a novel approach for optimizing pyrolysis conditions while providing theoretical guidance for designing efficient and selective pyrolysis processes.